Access to Justice for Disadvantaged Communities - Mayo, Marjorie (Book collections on Project MUSE., 2014)
This unique study explores how strategies to safeguard the provision of legal advice and access to welfare rights to disadvantaged communities might be developed in ways that strengthen rather than undermine the basic ethics and principles of public service provision.